Pengaruh Motivasi Dan Lokasi Wirausaha Terhadap Keberhasilan Usaha Toko Aksesoris Handphone Dalam Perspektif Ekonomi Islam - Annisa, Moza (Universitas Labuhanbatu, 2026)
This study examines the impact of motivation and location on business success at Toko Akse, Medan. Results indicate that both motivation and location significantly influence success, both individually and simultaneously. Strategic positioning and strong internal drive are essential for competitive advantage in the urban market. Future researchers are encouraged to explore additional variables to enhance understanding of entrepreneurial growth.